Winds at the 1000 - foot level and air pollution dispersion over the Kelang Valley region - Sham Sani, (Universiti Kebangsaan Malaysia, 1981)
Analysis of wind data for the 1000-foot at Subang Airport indicates that at night the wind flow is from Kuala Lumpur-Petaling Jaya towards Shah Alam, Kelang and Port Kelang. During the day, the flow pattern is reversed; the wind blows from the sea inland. Such patterns will inevitably affect air pollution dispersion at higher levels; at night pollutants from Kuala Lumpur-Petaling Jaya are transported downwind towards Shah Alam, Kelang and Port Kelang while in the daytime such pollutants are pushed back inland. The implications of this constrasting flow patterns towards air quality management in the Kelang Valley and their relevance to the Kuala Lumpur Master Plan were also discussed.